Toxic and hazardous waste disposal. - Pojasek, Robert B. (Ann Arbor Ann Arbor Science, 1979)
Contents: --v. 2. Options for stabilization/solidification --v. 4. New and promising ultimate disposal options.
Keywords: Factory and trade waste; Hazardous wastes